Adapting CBT for youth anxiety: Flexibility, within fidelity, in different settings - Kendall, Philip C.; Ney, Julia S.; Maxwell, Colleen A.; Lehrbach, Kyler R.; Jakubovic, Rafaella J.; McKnight, Dominique S.; Friedman, Abbey L. (Frontiers in Psychiatry, 2023)
Anxiety disorders are common in youth, associated with impairments in daily functioning, and often persist into adulthood when untreated. Cognitive behavioral therapy (CBT) for youth anxiety is a well-established intervention and has been modified to fit several treatment settings. Despite decades of results supporting the efficacy of CBT, there is a large gap in access to this treatment and a need to consider how it can best be administered flexibly to increase uptake and personalization. We first discuss the core components of treatment for CBT through the lens of the Coping Cat1 treatment. Next, we review the empirical findings regarding adjustments made for CBT for youth anxiety delivered (a) in schools, (b) in community settings, (c) through telehealth, (d) through online computer programs, and (e) by caregivers at home. In each setting, we provide specific suggestions for how to implement CBT with flexibility while maintaining fidelity.